Decreased Thyroxine Levels during rhGH Therapy in Children with Growth Hormone Deficiency - Ewelina Witkowska-Sędek (MDPI AG, 2021)
Background: Hypothyroidism in children leads to growth retardation. However, there is some evidence that recombinant human growth hormone (rhGH) therapy could suppress thyroid function. The most common observation in rhGH-treated patients is a decrease in thyroxine levels, which is reported as transient, but the studies in the field are inconsistent. We aimed to evaluate thyroid function in initially euthyroid children with idiopathic isolated GH deficiency during long-term rhGH therapy and to determine who is at a higher risk of thyroid function alterations during the therapy. Methods: The study group consisted of 101 children treated with rhGH for at least three years. Serum TSH and fT4 levels were determined at baseline, after the first six months and after each full year of therapy. The associations between changes in thyroid hormone levels during rhGH therapy and GH deficit, insulin-like growth factor-1 levels and growth response were investigated. Results: A significant decrease in fT4 levels (p = 0.01) was found as early as after the first six months of rhGH therapy. This effect persisted in the subsequent years of treatment without any significant changes in TSH values and tended to be rhGH dose related. Children with a greater fT4 decrease after the initiation of rhGH therapy were older, had higher bone age and responded to that therapy worse than children with lower fT4 changes. Conclusions: Our study revealed a long-term decrease in fT4 levels during rhGH therapy in initially euthyroid GHD children. The decrease in fT4 levels was associated with a lower growth response to rhGH therapy.